Interaction between Angiotensin II and Insulin/IGF-1 Exerted a Synergistic Stimulatory Effect on ERK1/2 Activation in Adrenocortical Carcinoma H295R Cells - An-li Tong; Fen Wang; Yun-ying Cui; Chun-yan Li; Yu-xiu Li (International Journal of Endocrinology)
The cross talk between angiotensin II (Ang II) and insulin has been described mainly in cardiovascular cells, hepatocytes, adipocytes, and so forth, and to date no such cross talk was reported in adrenal. In this study, we examined the interaction between Ang II and insulin/IGF-1 in ERK and AKT signaling pathways and expression of steroidogenic enzymes in H295R cells. Compared to the control, 100 nM Ang II increased phospho-ERK1/2 approximately 3-fold. Insulin (100 nM) or IGF-1 (10 nM) alone raised phospho-ERK1/2 1.8- and 1.5-fold, respectively, while, after pretreatment with 100 nM Ang II for 30 min, insulin (100 nM) or IGF-1 (10 nM) elevated phospho-ERK1/2 level 8- and 7-fold, respectively. The synergistic effect of Ang II and insulin/IGF-1 on ERK1/2 activation was inhibited by selective AT1 receptor blocker, PKC inhibitor, and MEK1/2 inhibitor. Ang II marginally suppressed AKT activation under the basal condition, while it had no effect on phospho-AKT induced by insulin/IGF-1. Ang II significantly stimulated mRNA expression of CYP11B1 and CYP11B2, and such stimulatory effects were enhanced when cells were cotreated with insulin/IGF-1. We are led to conclude that Ang II in combination with insulin/IGF-1 had an evident synergistic stimulatory effect on ERK1/2 activation in H295R cells and the effect may be responsible for the enhanced steroid hormone production induced by Ang II plus insulin/IGF-1.